Estimating Sensible and Latent Heat Fluxes over an Inland Water Body Using Optical and Microwave Scintillometers - Pierre, Adrien; Isabelle, Pierre-Erik; Nadeau, Daniel F.; Thiboult, Antoine; Perelet, Alexei; Rousseau, Alain N.; Anctil, François; Deschamps, Jaril (Boundary-layer meteorology, 2022)
Observations of turbulent heat fluxes over inland water bodies are scarce despite being critical to adequate lake parametrization for numerical weather forecast and climate models. Scintillometry has allowed for the regional (~ km 2 ) estimation of turbulent heat fluxes, but few studies have assessed its performance over water. We compare scintillometry-derived turbulent heat fluxes over an 85-km 2 dimictic boreal hydropower reservoir in eastern Canada (50.69° N, 63.24° W) with data from a raft-based eddy-covariance system. To the best of our knowledge, this is one of the first studies to quantify evaporation over an inland water body using a set of optical and microwave scintillometers. The scintillometer beam path extended 1.7 km over a section of the reservoir with depths of up to 100 m, from 14 August to 9 October 2019. Forty-nine days of data were retained. This study quantifies the impact of atmospheric stability on the derived fluxes and explores the use of temperature differences at the water–air interface from a point close to the centre of the scintillometer beam to properly estimate the direction of the sensible heat flux. The scintillometry approaches were well correlated with the eddy-covariance estimations for sensible heat fluxes ( R 2 up to 0.86, 32% bias), while the agreement decreased for latent heat fluxes ( R 2 up to 0.59, 69% bias). The scintillometer measured much larger latent heat fluxes than the eddy-covariance set-up. These results may be due to the larger footprint of the scintillometers capturing greater heterogeneity in the fluxes.